Weight and age at puberty of purebred and crossbred heifers grazing on natural pasture - Salomoni, Eduardo; Borba, Eber Rosa; Duca, Laudo Orestes Antunes Del; Leal, Joal José Brazzale (Pesquisa Agropecuaria Brasileira, 2014)
During a two-year period (June 1983 - June 1985) an experiment was carried on at UEPAE Bagé of EMBRAPA, in Bagé, RS, Brazil. The aim was to identify the age and liveweight at puberty of the lbagé crossbred heifers (3/8 Nelore-5/8 A. Angus) and compare them against the Hereford and Aberdeen Angus purebred, and also with intermediate crossbreeds obtained previously to reach the lbagé crossbreed. Fourty-two calves aged 7-8 months (seven animals per breed and blood degree) were used. They were maintained grazing on a native pasture in a 35 ha paddock on permanent daily vigilance for estrus detection. The randomized complete-block design was used for this experiment and the contrasts ware compared by using the Duncan's test. Correlation analyses also were used. The appearance of estrus was related to the negative pasture growth and also to the period of the animals liveweight gain. It was observed that animals with higher percentage of Aberdeen Angus blood reached puberty with lower age and liveweight than the other breeds and different blood degrees. The weights at 550 and 730 days and the liveweight gains up to this age have been negatively correlated with the puberty age. This showed that as higher the liveweight gained, the faster heifers reached the puberty, independently of the breed.